Application of BioFire FilmArray Blood Culture Identification panel for rapid identification of the causative agents of ventilator-associated pneumonia. (November 2018) - Pulido, M.R.; Moreno-Martínez, P.; González-Galán, V.; Fernández Cuenca, F.; Pascual, Á.; Garnacho-Montero, J.; Antonelli, M.; Dimopoulos, G.; Lepe, J.A.; McConnell, M.J.; Cisneros, J.M.; ,
Abstract: Objective: To evaluate the ability of the BioFire FilmArray Blood Culture Identification (BCID) panel to rapidly detect pathogens producing late-onset ventilator-associated pneumonia (VAP), a severe infection often produced by Gram-negative bacteria. These microorganisms are frequently multidrug resistant and typically require broad-spectrum empiric treatment. Methods: In the context of an international multicentre clinical trial (MagicBullet), respiratory samples were collected at the time of suspicion of VAP from 165 patients in 32 participating hospitals in Spain, Greece and Italy. Microorganisms were identified using the BCID panel and compared with results obtained by conventional microbiologic techniques. Results: Pseudomonas aeruginosa, Acinetobacter baumannii and Klebsiella pneumoniae were the most commonly identified species, representing 54.7% (70/128) of microorganisms. The BCID panel showed high global specificity (98.1%; 95% confidence interval, 96–100) and negative predictive values (96.6%) and a global sensitivity and positive predictive value of 78.6% (95% confidence interval, 70–88) and 87.3%, respectively, for these microorganisms. Importantly, the BCID panel provided results in only 1 hour directly from respiratory samples with minimal sample processing times. Conclusions: The BCID panel may have clinical utility in rapidly ruling out microorganisms causing VAP, specifically multidrug-resistant Gram-negative species. This could facilitate the optimization of empiric treatment.